Teaching methodologies used to inculcate islamic moral values in islamic education at Maktab Mahmud Pendang, Kedah : a case study - Fadhilah binti Mohd Salleh (Kulliyyah of Education, International Islamic University Malaysia, 2014)
Generally, the emphasis of Islamic education is on the wholesome development of children's personality and character in order to be a good vicegerent of Allah on earth. To be a Muslim requires that one's faith be reflected in one's practices and daily moral conduct with others. Yet many Muslims today do not live in accord with the Islamic principles and values of their faith. As the Islamic education is the core compulsory subject taken by all Muslim students, it shows that its contents are very significant in people's life. Thus, it is the responsibility of Muslim educators to develop teaching methodologies geared on making the learning of Islamic Education effective and meaningful for the Muslim students. This study aims to explore and investigate the teaching methodologies used in inculcating Islamic moral values in the Islamic Education at Maktab Mahmud Pendang, Kedah. The researcher employed a qualitative case study method to investigate in-depth the instructing methods used by the Islamic Education teachers in instilling Islamic moral values. The data were collected qualitatively through in-depth interview and observation. The participants of this study involved two Islamic Education teachers and two Form Five classes; 5 A (Account) and 5 B (Economy). Two selected students from each classes were the respondents for an interview session. Findings show that the Islamic Education teachers were inculcating various Islamic moral values through methods of lectures, group discussion, question and answer, storytelling, and drill and practice. The most popular teaching methods used by the Islamic Education teachers in this research were discussions and question and answer. The application of these methods were seen to affect some students' behavior in terms of motivating them to continue doing good deeds, helping them to evaluate and inculcate the Islamic values, and assisting them to develop students' responsibility toward their families and society.